2022
DOI: 10.1111/nep.14045
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 death and kidney disease in a multiracial Asian country

Abstract: Introduction COVID‐19 infection and kidney disease (KD) carry a considerable risk of mortality. Understanding predictors of death and KD may help improve management and patient outcome. Methods This is a prospective multicentre observational study conducted in a multiracial Asian country to identify predictors of death and acute kidney injury (AKI) in hospitalized COVID‐19 patients from January to June 2020. Results A total of 6078 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These findings concur with other reports indicating age as an independent predictor for AKI [14,36,37]. Furthermore, age has also been reported as a risk factor for death in COVID-19 patients [19,38], suggesting that elderly population is at a higher risk of morbidity and mortality, warranting special attention upon admission. In addition, similar to our study cohort, a retrospective study in London demonstrated a three-fold risk of AKI for patients who developed COVID-19 AKI with pre-existing CKD [16].…”
Section: Discussionsupporting
confidence: 91%
“…These findings concur with other reports indicating age as an independent predictor for AKI [14,36,37]. Furthermore, age has also been reported as a risk factor for death in COVID-19 patients [19,38], suggesting that elderly population is at a higher risk of morbidity and mortality, warranting special attention upon admission. In addition, similar to our study cohort, a retrospective study in London demonstrated a three-fold risk of AKI for patients who developed COVID-19 AKI with pre-existing CKD [16].…”
Section: Discussionsupporting
confidence: 91%
“…In a multi-centre Malaysian study, Chinese patients demonstrated a statistically significant higher mortality risk compared to Malays (aOR: 2.58; 95 % CI, 1.06–6.26). Conversely, Indians showed a reduced risk, despite being older with more comorbidities; however, this observation was not statistically significant (aOR: 0.25; 95 % CI: 0.03–2.10) [ 35 ]. Contrarily, a meta-analysis from the United Kingdom and Canada found that south Asians (SAs) had a 67 % higher risk of ICU admission than the general population, while Chinese individuals had a 28 % higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…From the published evidence, it is well proven that in CKD patients with COVID-19 the rates of hospitalization and death are higher ( Mirijello et al, 2021 ; Goh et al, 2022 ). These patients are more prone to adverse drug effects due to drug-drug reactions or altered pharmacokinetics and pharmacodynamics because of kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%